Dengue Hemorrhagic Fever with Acute Fulminant Hepatitis: A Case Report - M Adi Firmansyah (The Indonesian Society for Digestive Endoscopy, 2017)
Dengue virus is estimated to cause over 100 million infections throughout the world annually. Although dengue infections can have a wide range of clinical pictures, atypical manifestations have been described recent years. The liver is a susceptible organ affected in dengue infection. Mild liver dysfunction is common in cases of dengue infection but severe liver function impairment and even encephalopathy are rare. The following is a case report of dengue hemorrhagic fever (DHF) with acute fulminant hepatitis. A 43-year-old woman has fulminant hepatitis on day 3 of treatment. Her AST level increased dramatically from 363 U/L to 3,246 U/L. The causes of other hepatitis infection has been excluded. Her dengue IgM-antibody level was reactive. Level of dengue IgM antibody reactive. Clinical improvement experienced by patient after supportive therapy and administration glisirizin or Stronger Neo-Minophagen-C (SNMC).